Safety based Virtual Positioning System for Ad-Hoc Wireless Network - Gupta, Ganesh; Jaglan, Vivek; K Raghav, Ashok (International Journal of Engineering and Technology, 2018)
In the age of smart computing and advance global positioning system, it has been observed that day by day natural calamity affects our resources differently in regular way.  One of the most important tasks is to deploy ability for rescue inside infrastructure-less network in more accident prone area.  The security could be obtained through either automatic monitoring system or manually monitoring system by enabling several electronic means and sensors. Virtual positioning system is one of the most relevant computational areas where one can restrict unauthorized access while monitoring each one of single event more precisely.  This paper tries to add more security feature for a given Ad-Hoc wireless network area by utilizing SVPS (Secure Virtual Positioning System). In addition to it our proposed SVBS will be more effective security system to avoid hazards.
Keywords: 2D; 3D; AODV; CAD; Digital Aroma; GIS; Virtual Modeling; etc.